Effect of the Different COD/N Ratios on Multilevel Anaerobic/oxic Step-Feed Process for Integrated Removal of Carbon, Nitrogen and Phosphorus - Chen, Jieyun; Zhang, Zhi; Ren, Liping; Liu, Yaqin; Liang, Peng (Asian Journal of Chemistry, 2012)
The present object of this stuidy is to investigate the effect of the different COD/N ratio on multilevel anaerobic/oxic (A/O) step-feed process for nitrogen and phosphorus removal used actual life sewage. The experiment designed the fluctuation of influent C/N ratio ranging from 4 to 8 and studied the variation rules of COD, NH3-N, NO3-N, NO2-N, total nitrogen, total phosphorus in the multilevel A/O process. Results showed when the influent C/N ratio was from 4 to 8, the C/N ratio on the removal efficiencies of COD and NH3-N was not significant, and COD average removal efficiency was 89.2 %, NH3-N average removal efficiency was 96.5 %. But the influent C/N ratio on denitrification and biological phosphorus removal effect was obvious, the total nitrogen removal rate increased from 44.7 to 68.9 to 87.3 % when the influent C/N ratio increased from 4 to 6 to 8. In the absence of specialized set of anaerobic zone condition, the total phosphorus removal efficiency had worked in certain. The total phosphorus removal rate increased from 58.7 to 64.7 to 71.8 % when the influent C/N ratio increased from 4 to 6 to 8.when the influent C/N ratio was 8, the effluent total phosphorus is 0.86 mg/L.